Electro-Synthesis of Ultrafine V2AlC MAX-Phase and Its Conversion Process towards Two-Dimensional V2CTX. Issue 12 (6th August 2020) - Liu, Pengjie; Hou, Zhuoran; Hu, Mengjun; Hu, Liwen; Tang, Rong; Wu, Hongfei; Hu, Meilong
Abstract : V2 AlC is a typical ternary intermetallic compound and a precursor to synthesis 2D-MXenes V2 C. This work used cheap metal oxides and carbon as simple starting materials to fabricate MAX phases carbide V2 AlC by molten salt electrolysis, and the obtained product could be converted into 2D V2 C by a chemical etching process easily. The obtained ultrafine V2 AlC possess high purity and homogeneity, and the 2D V2 C from the chemical etching presented a unique layered Nano-sheets structure. TEM and X-ray photoelectron spectroscopy were combined to analysis the micromorphology and the chemical bonding states. And the reaction mechanism has been investigated to explore the facile synthetic method of V2 AlC and 2D V2 C.